Vuxenutbildningens distansundervisning: En villkorad flexibilitet - Åkerfeldt, Anna; Paul, Enni; Hrastinski, Stefan (Educare, 2025)
The Swedish municipal adult education curriculum emphasizes that there should be flexibility in education and accommodation to meet the adults’ diverse needs. However, it appears unclear what the concept of flexibility means in practice especially in the context of adult distance education. This study explores how the distance teacher role is constructed, how flexibility is enacted, and its implications for didactic practice. Drawing on focus groups with 46 teachers and principals and a mapping of seven municipal adult education activities, the findings reveal a paradox of conditional flexibility: while teachers are expected to be highly adaptable, organizational and economic constraints, standardized structures, and policy-driven efficiency goals limit real flexibility. Teachers navigate tensions between pedagogical ideals, administrative demands, and students’ expectations of autonomy, often at the cost of didactic quality. Assessment requirements further restrict flexibility, reinforcing rigid practices in a system that markets itself as flexible. The study argues for strategic organizational support and a redefinition of flexibility that prioritizes pedagogical and didactic dimensions.